The genome sequence of a sawfly, Abia candens Konow, 1887 [version 1; peer review: 2 approved] - Andrew Cunningham; Andrew Halstead (Wellcome Open Research)
We present a genome assembly from an individual male specimen of Abia candens (sawfly; Arthropoda; Insecta; Hymenoptera; Cimbicidae). The genome sequence has a total length of 261.00 megabases. Most of the assembly (82.7%) is scaffolded into 16 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 19.72 kilobases in length.